Teaching Specialised Translation Through Corpus Linguistics: Translation Quality Assessment and Methodology Evaluation and Enhancement by Experimental Approach - Kübler, Natalie; Mestivier, Alexandra; Pecman, Mojca (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2018)
In the current context of rapid and constant evolution of global communication and specialised discourses, the need for devising methods for ensuring both high quality levels of specialised translation and successful translation training is becoming a true challenge. Steady renewal in knowledge paradigms leads to an increase in term coinage, modifications in lexical and phraseological patterns, and accommodations in discourse conventions. This situation requires teachers in specialised translation to train future translators to develop the skills meant to help them adapt rapidly to change. The tools brought by corpus linguistics offer access to the language-in-the-making and continuously emerging knowledge fields. However, methods for their efficient exploitation in translation classes can still be improved. In the current study, we present the translation-teaching framework devised specifically for such contexts. It is based on corpus linguistics, terminology management, collaboration with experts, and the quantitative analysis of the quality of finished translations, which can then, in turn, be used to improve the overall framework and to provide research material on specialised translation problems.